An evaluation of undergraduate student nurses' gameful experience whilst playing a digital escape room as part of a FIRST year module: A cross-sectional study. (November 2022) - Antón-Solanas, Isabel; Rodríguez-Roca, Beatriz; Urcola-Pardo, Fernando; Anguas-Gracia, Ana; Satústegui-Dordá, Pedro J.; Echániz-Serrano, Emmanuel; Subirón-Valera, Ana B.
Abstract: Background: The circumstances arising from the COVID-19 pandemic have accelerated the use of digital teaching and learning in health professions education. Digital gamification-based teaching and learning activities are innovative and versatile tools for the acquisition of professional competencies in higher education, which can be used on a range of topics and can be supplemental to other teaching methods. Objectives: This study aimed to investigate nursing students' gameful experience whilst playing a digital escape room. In addition, we aimed to analyze the students' motivation, learning experience and outcome of the activity, and the students' perception of the degree of achievement of the intended learning outcomes. Design: Cross-sectional descriptive study. Participants: A total of 136 undergraduate first year student nurses enrolled in a "Fundamentals of Nursing" course. Method: The digital escape room game took place online during the academic year 2020–2021. The measures included the GAMEX scale in its Spanish version and a self-reported questionnaire to evaluate the outcome of the scape room game and the degree of achievement of the intended learning outcomes. Results: More than 80 % of the participants were moderately to very motivated to play the game. Three GAMEX dimensions achieved a mean score of 3 or above 3, namely Enjoyment, Creative Thinking and Absence of Negative effects. The mean score for each of the outcome variables was over 3. However, the degree of achievement of the learning outcomes after exiting the digital escape room was uneven. Conclusion: Gamification-based teaching and learning activities, such as digital escape rooms, can be effective in fostering specific skills, including teamwork, communication and critical thinking. However, they should be designed carefully, and used as a complement, rather than a substitute, of other educational activities. Highlights: Playing a digital escape room can be a positive learning experience improving student capacity to apply nursing knowledge. Digital escape rooms can be effective in fostering specific skills, including teamwork, communication and critical thinking. Gamification-based activities should be designed carefully and used as a complement of other educational activities.